Proceedings of the 21st International Conference on Computational Linguistics and the 44th Annual Meeting of the ACL - ACL '06 2006
DOI: 10.3115/1220175.1220289
|View full text |Cite
|
Sign up to set email alerts
|

Methods for using textual entailment in open-domain question answering

Abstract: Work on the semantics of questions has argued that the relation between a question and its answer(s) can be cast in terms of logical entailment. In this paper, we demonstrate how computational systems designed to recognize textual entailment can be used to enhance the accuracy of current open-domain automatic question answering (Q/A) systems. In our experiments, we show that when textual entailment information is used to either filter or rank answers returned by a Q/A system, accuracy can be increased by as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(88 citation statements)
references
References 14 publications
0
86
0
2
Order By: Relevance
“…A fundamental motivation and long standing goal of the paraphrasing and RTE communities has been to cast various semantic applications as paraphrasing/textual entailment (Dagan et al, 2013). While it has been shown that paraphrasing methods are useful for question answering (Harabagiu and Hickl, 2006) and relation extraction (Romano et al, 2006), this is, to the best of our knowledge, the first paper to perform semantic parsing through paraphrasing. Our paraphrase model emphasizes simplicity and efficiency, but the framework is agnostic to the internals of the paraphrase method.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental motivation and long standing goal of the paraphrasing and RTE communities has been to cast various semantic applications as paraphrasing/textual entailment (Dagan et al, 2013). While it has been shown that paraphrasing methods are useful for question answering (Harabagiu and Hickl, 2006) and relation extraction (Romano et al, 2006), this is, to the best of our knowledge, the first paper to perform semantic parsing through paraphrasing. Our paraphrase model emphasizes simplicity and efficiency, but the framework is agnostic to the internals of the paraphrase method.…”
Section: Discussionmentioning
confidence: 99%
“…Punyakanok et al (2004) compute the tree edit distance between the dependency trees of the question and answer, and Bouma et al (2005) use deep syntactic parsing and distributional similarities from external corpora). Even though results to the RTE task in general were modest with accuracy scores between 50-60%, for specific task settings, they could bring accuracy gains: Harabagiu (2006) report an increase in performance from 30.6% to 42.7% on an open-domain QA task.…”
Section: Related Workmentioning
confidence: 99%
“…Some recent works [5] have shown how the use of textual entailment can improve the accuracy of QA systems. Our aim was to obtain evidences of this improvement in a comparative and shared evaluation.…”
Section: Evaluation Of the Answer Validation Exercisementioning
confidence: 99%
“…In some sense, systems must emulate human assessment of QA responses and decide whether an answer is correct or not according to a given text. This automatic Answer Validation is expected to be useful for improving QA systems performance [5]. However, the evaluation methodology in AVE 2006 did not permit to quantify this improvement and thus, the exercise has been modified in AVE 2007.…”
Section: Introductionmentioning
confidence: 99%